Mirror, Peephole and Video – The Role of Contiguity in Children’s Perception of Reference in Iconic Signs - Lenninger, Sara; Persson, Tomas; van de Weijer, Joost; Sonesson, Göran (Frontiers in Psychology, 2020)
The present study looked at the extent to which 2-year-old children benefited from information conveyed by viewing a hiding event through an opening in a cardboard screen, seeing it as live video, as pre-recorded video, or by way of a mirror. Being encouraged to find the hidden object by selecting one out of two cups, the children successfully picked the baited cup significantly more often when they had viewed the hiding through the opening, or in live video, than when they viewed it in pre-recorded video, or by way of a mirror. All conditions rely on the perception of similarity. The study suggests, however, that contiguity – i.e., the perception of temporal and physical closeness between events – rather than similarity is the principal factor accounting for the results.